Novel Vaccine Technologies in Veterinary Medicine: A Herald to Human Medicine Vaccines - Aida, Virginia; Pliasas, Vasilis C.; Neasham, Peter J.; North, J. Fletcher; McWhorter, Kirklin L.; Glover, Sheniqua R.; Kyriakis, Constantinos S. (Frontiers in Veterinary Science, 2021)
The success of inactivated and live-attenuated vaccines has enhanced livestock productivity, promoted food security, and attenuated the morbidity and mortality of several human, animal, and zoonotic diseases. However, these traditional vaccine technologies are not without fault. The efficacy of inactivated vaccines can be suboptimal with particular pathogens and safety concerns arise with live-attenuated vaccines. Additionally, the rate of emerging infectious diseases continues to increase and with that the need to quickly deploy new vaccines. Unfortunately, first generation vaccines are not conducive to such urgencies. Within the last three decades, veterinary medicine has spearheaded the advancement in novel vaccine development to circumvent several of the flaws associated with classical vaccines. These third generation vaccines, including DNA, RNA and recombinant viral-vector vaccines, induce both humoral and cellular immune response, are economically manufactured, safe to use, and can be utilized to differentiate infected from vaccinated animals. The present article offers a review of commercially available novel vaccine technologies currently utilized in companion animal, food animal, and wildlife disease control.